2022
DOI: 10.3389/fcvm.2022.867732
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Results of the Modified Bentall Procedure With Mechanical and Biological Composite Valve Grafts

Abstract: ObjectivesDespite the evident shift toward biological prostheses, the optimal choice of valve remains controversial in composite valve graft (CVG) replacement. We investigated long-term morbidity and mortality after CVG implantation in an all-comer cohort with a subgroup analysis of patients aged 50–70 years stratified after valve type.MethodsA total of 507 patients underwent the Bentall procedure with either a mechanical (MCVG, n = 299) or a biological (BCVG n = 208) CVG replacement between 2000 and 2020. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…After excluding duplicates and noneligible studies, 23 studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 met our eligibility criteria (Figure 1 ), including a total of 11 428 patients (3786 patients with mechanical valves and 7642 patients with bioprosthetic valve). All the studies were nonrandomized and observational.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and noneligible studies, 23 studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 met our eligibility criteria (Figure 1 ), including a total of 11 428 patients (3786 patients with mechanical valves and 7642 patients with bioprosthetic valve). All the studies were nonrandomized and observational.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were nonrandomized and observational. Characteristics of the studies and patients are shown in Tables 1 and 2 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 respectively. The overall population was mostly composed of men (mean age ranging from 45.5 to 75.6 years) with a considerable prevalence of bicuspid aortic valve disease (ranging from 3.1% to 100.0%) and connective tissue disorders (ranging from 1.6% to 34.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hiện nay, việc lựa chọn giữa van cơ học và van sinh học được quyết định theo từng cá thể mà không còn phụ thuộc chủ yếu vào độ tuổi (tuổi được khuyến cáo ưu tiên dùng van cơ học theo ACC/AHA là <50, và ESC là <60 tuổi) 9,10 . Mặc dù loại van tối ưu đối với nhóm BN trong độ tuổi từ 50 -70 vẫn là chủ đề được tranh luận trong nhiều thập kỷ trở lại đây, theo Werner và cộng sự loại ống van được lựa chọn không ảnh hưởng ý nghĩa đến tỉ lệ tử vong trong nhóm BN này 4 . Các thử nghiệm ngẫu nhiên giữa nhóm dùng van cơ học và nhóm dùng van sinh học không cho thấy có sự khác biệt về tỉ lệ sống, tỉ lệ huyết khối van và tỉ lệ thuyên tắc, nhóm dùng van cơ học có tỉ lệ chảy máu cao hơn trong khi tỉ lệ cần can thiệp lại cao hơn ở nhóm dùng van sinh học 11 .…”
Section: Bàn Luậnunclassified
“…Karangelis và cộng sự 2 nhận xét tỉ lệ mổ lại do chảy máu là 5,6% và tỉ lệ suy thận nặng cần lọc máu là 5,6%. Theo Werner và cộng sự 4 tỉ lệ mổ lại do chảy máu là 6,5%, tỉ lệ tai biến mạch não là 4,7%. Chúng tôi cũng ghi nhận những kết quả tương tự với tỉ lệ mổ lại do chảy máu là 7,7% và tỉ lệ suy thận nặng là 7,7%.…”
Section: Bàn Luậnunclassified